The absolute configuration of 1-epialexine hemihydrate. - Thompson, A; Watkin, D; Gal, Z; Jones, L; Hollinshead, J; Jenkinson, S; Fleet, G; Nash, R (2008)
The absolute and relative configurations of 1-epialexine are established by X-ray crystallographic analysis, giving (1S,2R,3R,7S,7aS)-1,2,7-trihydroxy-3-(hydroxymethyl)pyrrolizidine. The compound crystallizes as the hemihydrate C(8)H(15)NO(4) x 0.5H(2)O, with hydrogen bonds holding the water molecule in a hydrophilic pocket between epialexine bilayers. In addition, a comparison was made between results obtained from examination of the Bijvoet pairs from data sets collected using molybdenum and copper radiation.